Profil Jaringan Irigasis Berbasis Peta Digital Di Desa Kema Satu Kecamatan Kema Kabupaten Minahasa Utara - dahlan; Molenaar, Robert; Rantung, Ruland A. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2024)
This research uses a descriptive method by collecting data through field surveys, interviews and image analysis. The research results show that the Makansar irrigation network in Kema Satu Village consists of one main weir and three supply channels. The Makansar Satu Dam (BM I) irrigation channel is 3,129.53 ms long with a service area of 11.42 hectares. The Water Suplesi Satu (AS I) canal has a length of 1,885.36 ms and a service area of 10.22 hectares, the Water Suplesi Two irrigation canal (AS II) has a length of 544.26 and a service area of 1.77 hectares, the Water Suplesi Three irrigation canal ( AS III) has a length of 1,878.8 and a service area of 6.88 hectares. There are around 33 buildings along the irrigation canal, including 1 building, 24 tapping buildings, 7 complementary buildings, 1 tertiary box, and 1 spillway building. The condition of the network and buildings still requires a lot of technical treatment and a decline in the quality of services at the old weir, the growth of wild plants on the irrigation embankment, the presence of sedimentation and complementary buildings that are not utilized properly as water conservation efforts. The Makasar irrigation area (DI) has a P3A institution. The results of measuring the water discharge in the BM I Channel, the inflow was 0.23 m3/second and the outflow was 0.09 m3/second and the water loss was 0.14 m3/second. Measurements in the Channel (AS I) inflow were 0.07 m3/second and outflow 0.07 m3/second. Channel measurements (AS III) showed an inflow value of 0.03 m3/second and an outflow of 0.02 m3/second and water loss of 0.01 m3/second.